2020
DOI: 10.1186/s12877-020-01845-9
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of medication-related fall risk in fall risk assessment tool in geriatric care units

Abstract: Background Falls are common undesirable events for older adults in institutions. Even though the patient’s fall risk may be scored on admission, the medication-induced fall risk may be ignored. This study developed a preliminary categorization of fall-risk-increasing drugs (FRIDs) to be added as a risk factor to the existing fall risk assessment tool routinely used in geriatric care units. Methods Medication use data of older adults who had experienced at least one fall during a hospital ward or a nursing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…51 Another study, also conducted in the Portuguese population, found that the pharmacological groups of PIMs with the highest prescription were anxiolytics, more precisely derivatives of benzodiazepines, antidepressants, antipsychotics and proton-pump inhibitors. 52 Although the literature associates medication use with increased risk of falls, 53 , 54 we found no significant relationships between the presence of PIMs and the occurrence of falls.…”
Section: Discussionmentioning
confidence: 56%
“…51 Another study, also conducted in the Portuguese population, found that the pharmacological groups of PIMs with the highest prescription were anxiolytics, more precisely derivatives of benzodiazepines, antidepressants, antipsychotics and proton-pump inhibitors. 52 Although the literature associates medication use with increased risk of falls, 53 , 54 we found no significant relationships between the presence of PIMs and the occurrence of falls.…”
Section: Discussionmentioning
confidence: 56%
“…Partly because of possible fluctuations in blood pressure and partly because of the mechanism of drug action, cardiovascular diseases increase not only the risk but also the severity of falls [11,19,20]. The risk of falls rises by 60% when using antiarrhythmic calcium channel blockers; by 20% when taking drugs containing digoxin; and by 10% when taking diuretics [15,21]. Based on our sample data and data for the elderly population living at home, it can be stated that one in two elderly people suffer from cardiovascular disease [22].…”
Section: Chronic Diseasesmentioning
confidence: 99%
“…This increased risk is due partly to the side effects of the drugs and partly to drug interactions. The risk of falling is 66% higher when taking psychoactive drugs [21,22,37]. In terms of medication, the most common cause of falls is the regular use of antidepressants: serotonin reuptake inhibitors in particular increase the risk of falls [38].…”
Section: Chronic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, regarding the risk factors for falls and/or fractures and in the context of clinical comorbidities, there is limited published research that seeks to establish a comprehensive model of factors that influence fall and fracture risk among elderly patients. 15,16 Given the gaps in evidence around these common adverse events associated with opioid use, this study sought to assess the frequency, time to event, and risk factors associated with a fall or fracture in a commercially insured US population of patients with OA taking opioids (ie, tramadol or non-tramadol opioids).…”
Section: Introductionmentioning
confidence: 99%